Risk factors affecting software projects in South Africa - D. Smith; M. Eastcroft; N. Mahmood; H. Rode (South African Journal of Business Management, 2006)
This paper reports on an analysis of risk factors relevant to South African software projects. Seven of the most widely cited studies in the research literature regarding software project risk were evaluated along with a detailed examination of the 53 risk factors developed by Schmidt, Lyytinen, Keil Cule (2001). Forty completed questionnaires, submitted by software project managers, were analysed.The main findings of this research were:Project managers of varying experience perceived different software risks to be important Risks relating to quality, cost, time, requirements or methodology were not perceived to be more important than risks relating to people, relationships or change) by project managersThe top ten most important risks as perceived by project managers were:Lack of top management commitment to the projectUnclear/ misunderstood scope/ objectives Schedule Flaw Lack of client responsibility, ownership and buy-in of the project and it's delivered systems No planning or inadequate planning Project not based on sound business case Lack of available skilled personnel Not managing change properly Lack of adequate user involvement Poor risk managementFrom this list it was noted that risks number 5, 6, 7 and 8 were unique to this study and were not found in prior studies in the research literature. It was concluded that the importance of these risks may be unique to South African software projects.
Keywords: 650